EVALUATION OF POLICY AND RESOLUTION STRATEGIES IN THE BANGKA ISLANDS - Septian Abdillah Harys (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Illegal tin mining activities in the Bangka Islands have shifted from merely an economic or environmental issue to a serious challenge for Indonesia’s national security, triggering both horizontal and vertical social conflicts that threaten regional stability. This study aims to: (1) analyze the authority of local governments in addressing illegal mining as a form of policy evaluation; (2) identify the implications of the conflicts and the resolution efforts undertaken; and (3) evaluate these measures to support national security. Using an Exploratory Descriptive Qualitative approach, data were collected through in-depth interviews, observations, and document studies in key illegal mining areas in Bangka Regency and Central Bangka Regency. The conflict resolution framework (Susskind, 1994) and the concept of National Security (Slawotsky, 2024) serve as analytical lenses to bridge the gap between the normative framework of Law Number 7 of 2012 on Social Conflict Management and field realities. The expected outcome is the formulation of conflict resolution strategies that are applicable, transparent, participatory, and grounded in ecological justice in order to restore effective state control and strengthen national security stability.